Cardiotropic action of combined use of celecoxib and amlodipine in rats sicked on adjuvant arthritis coupled with arterial hypertension - N. N. Seredinskaya; A. A. Sushinskaya; V. S. Chomenko; Z. P. Omelyanenko; T. A. Bershova (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Drug therapy of rheumatoid arthritis combined with arterial hypertension is among actual medical objectives. The complexity of pharmacological treatment of comorbid state is due to not only pathological process severity, insufficient efficacy and side effects of disease modifying and symptomatic drugs but also property of nonsteroidal anti-inflammatory drugs (NSAIDs) to aggravate already existed arterial hypertension in patients with rheumatoid arthritis or to increase pressure. Many hypotensive drugs loose or don't manifest their activity when used in combination with NSAIDs. High risk of cardio toxicity is registered for one of NSAIDs group - coxibs. The cardio safety of combined use of coxibs and hypotensive drugs on the ground of comorbid pathology is studied not enough. These aspects had predefined the aim of this study - to investigate cardiotropic effects of celecoxib when administered in combinations with amlodipine on the ground of experimental rheumatoid arthritis coupled with arterial hypertension. Arterial hypertension was modeled in rats by method of salt load. On the basis of arterial hypertension rheumatoid arthritis was caused by full Freund adjuvant injection. Arterial blood pressure and heart rate registered on sphygmomanometer. It was found that comorbid state is followed by arterial hypertension and tachyarrhythmia. Celecoxib does not facilitate hypertension enhancing but leads to increasing heart rate. Amlodipine manifests specific pharmacological activity as hypotensive drug. The results obtained predefined opportunity of combined use of celecoxib with amlodipine on the ground of rheumatoid arthritis coupled with arterial hypertension.